Use of Biochemical Indicators to Evaluate The Nutritional Status of Lactating Cows - D. A. Astuti; D. R. Ekastuti; D. Sastradipradja; Suryahadi (Suryahadi) (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy